HUBUNGAN LITERASI DIGITAL DENGAN PERILAKU KEAMANAN SIBER PADA MAHASISWA PERPUSTAKAAN DAN SAINS INFORMASI UNIVERSITAS PADJADJARAN - Oktapiyadi, Wandi; Saepudin, Encang; Yanto, Andri (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2024)
This research aims to find the relationship between digital literacy and cybersecurity behavior among Library and Information Science students in Universitas Padjadjaran. The concept of digital literacy used in this research is based on three dimensions, including technical, cognitive and social-emotional dimensions. This study used a quantitative method with correlational approach, that attempts to analyze the relationship between two or more variables and the strength of the relationship. 75 students from classes of 2020, 2021 and 2022 in the department have been selected as the target of this study with simple random sampling technique. The results of the research show that the three dimensions, namely technical, cognitive and socio-emotional dimensions, all are having a significant relationship with cybersecurity behavior. The three are also having a low level of relationship when it comes to cybersecurity behavior. Based on the results, it can be concluded that digital literacy has a significant relationship with cybersecurity behavior, despite the level of the relationship between the two are low. Which also means that a high level of digital literacy doesn’t guarantee good cybersecurity behavior either.